Cognitive impairment in HIV and HCV co-infected patients: a systematic review and meta-analysis. Issue 12 (1st December 2016) - Fialho, Renata; Pereira, Marco; Bucur, Mihaela; Fisher, Martin; Whale, Richard; Rusted, Jennifer
ABSTRACT: Cognitive impairment has been well documented in human immunodeficiency virus (HIV) and hepatitis C virus (HCV) mono-infections. However, in the context of HIV/HCV co-infection the research is more limited. The aim of this systematic review was to describe the characteristics of cognitive impairment in HIV/HCV co-infection and to examine the differences in cognitive performance between HIV/HCV and HIV and HCV mono-infected patients. Of the 437 records initially screened, 24 papers met the inclusion criteria and were included in the systematic review. Four studies were included in the meta-analysis. Most studies indicated that HIV/HCV co-infected patients had a higher level of cognitive impairment than HIV mono-infected patients. Meta-analysis also indicated that HIV mono-infected patients had a significantly lower global deficit score than co-infected patients. The results also indicated that co-infected patients were more likely to be impaired in information processing speed than HIV mono-infected patients. These findings can be challenged by biasing factors such as the small number of included studies, heterogeneity of the samples and a large diversity of methodological procedures. Future research with consistent and comprehensive neuropsychological batteries and covering a greater diversity of risk factors is needed, in order to clarify the effects of both viruses on cognitive function and the mechanisms that underlie these effects. Because cognitive impairments may pose significant challenges to medication adherence, quality of life and overall functioning, such knowledge may have important implications to the planning and implementation of effective interventions aimed at optimising the clinical management of these infections.